Where the wild things are - Sendak, Maurice (New York : Scholastic, 1983)
A naughty little boy, sent to bed without his supper, dreams about sailing to the land of the wild things where he becomes their king.
Mode of access: Internet.
Keywords: Monsters -- Juvenile fiction; Fantasy -- Juvenile fiction